Navigating Early Marriages: A Methodological Breakthrough in Family Resilience Measurement - Qomaro, Galuh Widitya; Nasrulloh, Nasrulloh; Hasyim, Muh. Fathoni; Nur, Iffatin (Mazahib, 2024)
This article explores early marriage in Madura. Early marriage causes psychological problems and physical and material losses that are not in line with the purpose of family formation in Islam. Using a mixed method approach, this article utilizes questionnaires, interviews, observations, and documentation obtained using Structural Equation Modeling with the Partial Least Square approach equipped with qualitative analysis. The achievement of family formation goals is measured using Maqāsid Al-Usrah indicators by Jamal Al-Din 'Atiyah Muhammad. The measurement results indicate that early marriage families in the Madura Muslim community achieve family formation goals to ensure human life continuity, regulate male-female relationships, maintain lineage clarity, and preserve religiosity within the family. At a methodological level, this research contributes to various models for measuring family resilience in establishing and building a family. Based on reliability and validity tests, all indicators of maqāsid al-usrah’s Jamal Al-Din ‘Atiyah Muhammad are declared valid and reliable so that they can be used to measure the achievement of family formation goals in other subjects in further research studies.